Preliminary Indications That First Semester Students From Academic Households Exhibit Higher Hair Cortisol Concentrations Than Their Peers From Nonacademic Households - Bertrams, Alex; Minkley, Nina (Frontiers in Psychiatry, 2020)
Previous research has extensively addressed social disparity in education using certain aspects, including the stress differences between students from nonacademic families and those from academic families during the transition from secondary school to a university. However, this issue has not yet been fully understood; the current literature suggests contradictory predictions, and physiological indicators of stress have never been assessed. Therefore, we tested whether hair cortisol concentrations (HCCs) in first semester students from nonacademic families are different from those of first semester students from academic families during their first six weeks at university. We analyzed hair samples and parental educational background reports from 71 female first semester students at a university in Switzerland in two waves (n = 34 in the autumn of 2016 and n = 37 in the autumn of 2017). The HCCs were extracted from the hair using a well-established protocol. The analyses revealed higher HCCs in the students from the academic families across the two cohorts. This difference could not be attributed to different control variables (e.g., age, migration background). These preliminary findings were in line with the sociological theory that an academic parental background is associated with pressure to avoid a drop in one’s social status.